ANALISIS MATERI YOUTUBE USEFUL GERMAN WITH CHRIS SEBAGAI BAHAN AJAR KETERAMPILAN BERBICARA KELAS XII SEMESTER 1 - Ramadhani, Cornelia; Wahyuningsih, Fahmi (LATERNE, 2022)
Currently learning German speaking skills is considered very lacking, it is proven by the number of students who are still wrong in pronouncing Wortschatz and Redemittel. This can be overcome by using appropriate methods, teaching materials, and learning media. In the current technological era, the use of YouTube as a multimedia-based teaching material is favored by most of Generation Z. One of the YouTube that can be used as teaching materials to improve students’s German speaking skills is the Useful German with Chris. This channel contains a variety of German learning materials that can be easily accessed anytime and anywhere, there are various themes in each video, it contains interesting animations and sounds filled by native German speakers so that it can be a clear example for students to learn. imitate the words correctly. In this article, the analyzed video is entitled Meine Hobbys. The formulation of the problem in this article is how the content of the - Meine Hobbys video as teaching material for German speaking skills for class XII odd semester students based on the 2013 curriculum. Chris withThe 2013 curriculum is for odd semester 12th graders with storytelling speaking skills related to the theme Freizeitbesch?ftigung und Hobbys. The writing in this article is processed with qualitative descriptive. The source of data in this study is the youtube Useful German with Chris - Meine Hobbys, dan data This research was collected from the content of the video content in the form of oral discourse containing Wortschatz and Redemittel. The technique used in this study is the listening technique, then continued with the note-taking technique for recording something that has been listened to in writing. After all the data has been collected, the next step is data analysis using content analysis techniques by analyzing the suitability between the material items from the video content and the material for the odd semester class XII students with the Freizeitbesch?ftigung und Hobby contained in the 2013 Curriculum. 80% conformity. So with this percentage figure, the YouTube video Useful German with Chris is concluded to be very suitable as teaching material for speaking skills with the type of storytelling with the theme Freizeitbesch?ftigung und Hobby for class XII students in First semester.